2012
DOI: 10.4012/dmj.2012-079
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence properties of commercial composite resin restorative materials in dentistry

Abstract: The objective was to assess the fluorescence properties of current commercial resin composites. Sixteen light-curing resin composites, representing a total number of 241 shades, were analyzed. Fluorescence measurements of all samples were taken using the monochromator-based fluorescence reader Synergy TM Mx (BioTek Instruments Inc.). Additionally, samples of dentin and enamel were analyzed for comparison. The mean of the maximum excitation wavelength was (398±5) nm and the mean of the resulting emission wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 32 publications
(48 reference statements)
4
93
2
2
Order By: Relevance
“…This aligns with results of previous studies analyzing composite resin materials [11,23] which showed that optimal excitation wavelengths for the composite resin materials used in their studies were in the range of 365 -380nm and 398 ± 5 nm, respectively. Fluorescence properties of materials in the mouth can be affected by the ingress of moisture as well as by degradation over time.…”
Section: Discussionsupporting
confidence: 90%
“…This aligns with results of previous studies analyzing composite resin materials [11,23] which showed that optimal excitation wavelengths for the composite resin materials used in their studies were in the range of 365 -380nm and 398 ± 5 nm, respectively. Fluorescence properties of materials in the mouth can be affected by the ingress of moisture as well as by degradation over time.…”
Section: Discussionsupporting
confidence: 90%
“…Although there are some differences in the fluorescence properties of the materials, it remains reserved, whether these differences have any influence on proper colour matching in clinical application 24) . This has to be investigated in further in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Essa diferença de achados pode ser atribuída às marcas comerciais escolhidas nos diferentes trabalhos, uma vez que apresentam diferentes composições [3] .…”
Section: Valores Médios De Fluorescência Para Resinas De Esmalteunclassified
“…Entretanto, devido à mudança da iluminação, esses materiais se comportam de formas diferentes. Sendo assim, o cirurgião dentista necessita compreender como se manifestam os materiais restauradores e as estruturas dentais sob diferentes fontes de luz [3] .…”
Section: Introductionunclassified